Karthickia verestigmata gen. et sp. nov. – an interesting diatom with frustular morphology similar to several different cymbelloid diatom genera. Issue 6 (2nd November 2019) - Glushchenko, Anton; Kuznetsova, Irina; Kociolek, John Patrick; Kulikovskiy, Maxim
ABSTRACT: Light and scanning electron microscope observations are presented for Karthickia verestigmata gen. et sp. nov . The taxon is described from Laos and Vietnam. This diatom has features that would suggest similarities with Cymbopleura, Cymbella and Oricymba . The new taxon is characterised by the presence of a single external stigma opening that has two elongated slit-like openings internally, residing within two longer central striae. These slit-like furrows occupied one-third of stria length near the central area. The presence of a stigma suggests a relationship of this species with genera such as like Cymbella and Oricymba, and the single external opening with two internal openings is similar to that in Oricymba . Internally, areolae are covered by tectulla that are not typical for Cymbopleura but known in species of Cymbella as well as Gomphonema . The morphological features of this unique taxon lead us to conclude that it is best accommodated in a new genus.